The Control of Pathogenic Fungi with Trichoderma in Banjar Pinge, Tabanan of Bali Province - A. A. S. P. R. Andriani; I Gusti Made Arjana; Luh Kartini; Dewa Gede Wiryangga Selangga; Ismail Rakibe (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Pinge is one of the traditional sub-village (banjar) in Baru Village, Marga Sub district, Tabanan Regency of Bali Province. There are 36% of villagers living below the poverty line where 85% of them are farmers who cultivate fruit and flowers. They have many problems with fruit and flower production as the yields is low due to natural disasters and poor agricultural practice and support. Some flower growers often complain of low flower production, especially Marigold flowers due to the attack of pathogenic fungi that cause flower blight. The solution to solve the problems faced by partners is: by providing Appropriate Technology in the processing of cow dung into compost fertilizer plus trichoderma sp antagonist microorganisms. External targets to be achieved are the use of appropriate technology in the processing technology of cow dung into compost plus Trichoderma sp. Based on the results of activities as much as 70% understand and are able to apply pest and disease control to flowers by utilizing biological agents. Trichoderma can reduce the intensity of disease above the ground by 50.00% and suppress the intensity in the soil by 34.48%. In addition, giving Trichoderma sp. can increase the fresh weight of the plant by up to 30.75%.